African folktales : traditional stories of the Black world - Abrahams, Roger D. (New York : Pantheon Books, 1983)
A collection of African folktales, drawing on a wide range of sources, from the notes of early missionaries to contemporary works of anthropologists and ethnographers.
Includes bibliographical references (p. 343-346) and index.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Folklore -- Africa; Folklore -- Africa